POLSKA POLITYKA HISTORYCZNA W OCENIE ZYGMUNTA WOJCIECHOWSKIEGO W OKRESIE MIĘDZYWOJENNYM - Marszał, Maciej (Zeszyty Prawnicze, 2016)
Zygmunt Wojciechowski’s Assessment of the History-Based Policy in the Interwar Period Summary This paper will provide an analysis of the History-Based Politics in thoughts of Zygmunt Wojciechowski (1900–1955) – history profesor at the University of Poznań, co-founder of the Baltic Institute (Instytut Bałtycki) in Toruń, publicist of the “Avant-garde” and expert on PolishGerman relations. Wojciechowski in Polish political thought was a representative of the Integral Polish nationalism (polski nacjonalizm integralny), which meant synthesis of national and state’s demands. He opted for the ideological formula in order to reach an agreement between the political heritage of Roman Dmowski and the Józef Piłsudski’s political reforms. For Wojciechowski, a professor of history, an important element of national consciousness was the historical awareness that the Polish state must continuously maintain through History-Based Policy. According to him, this policy should focus on three main issues: First, the expansion on the tradition referring to the beginning of Polish statehood. Second issue would be to make Poles aware of their international situation, especially in the context of their struggle with the Germanic and Prussian element. And the third issue would be to revise and update the values of the Constitution of May 3. It should be noted that the views of Zygmunt Wojciechowski on History-Based Policy in the interwar period were a part of a political discourse. His bold and uncompromising thoughts of the Polish-German relations and the demand to return the “Lands of Piasts” (ziemie Piastów) constituted an important element of the Integral Polish nationalism. It wouldn’t be too far-fetched to say that the desire to carry-on the political will of Jan Ludwik Popławski and bring the Poles back to their “ancestral lands” (ziemie macierzyste) was present in Polish historical consciousness of the interwar period.